Infared charge modulation spectroscopy of organic field-effect transistor. - Chin, Xin Yu. (2012)
Charge modulation spectroscopy (CMS) is an electrical pump-optical probe technique for the in situ probing of charge carrier transport in organic field-effect transistors (OFETs). CMS is a powerful tool to measure characteristics of charge carriers, such as their kind and the concentration, and provides results that are comparable to interfacial or photo-doping. The primary advantage of this technique is that it can be implemented in actual electronic device structures. While usually CMS is carried out by probing the signatures of polaronic states in the near-infrared spectral region, which are somehow non-specific and masked by excitonic transitions, in this work we performed CMS in the medium infrared, which provides a more direct probe of the charge carriers present at the interface of the semiconductor. OFETs with regioregular-poly(3-hexylthiophene) active material were fabricated. Electro-induced CMS reflectance spectra were measured between 680 and 4000 cm-1 using a Fourier Transform Infra-Red (FTIR) spectrometer, revealing Infra-Red Active Vibrational (IRAV) modes due to the polarons induced by electrostatic doping. The obtained CMS spectra show a one-to-one correspondence with the IRAV modes measured by photoinduced absorption at relatively high photon fluence, proving the robustness of the method and its high sensitivity. Spatial mapping of the OFET channel was further implemented using an IR confocal microscope to obtain the charge carrier density distribution and its dependence on applied drain-source bias. This work demonstrates the potential of infrared CMS as a tool to characterize charge carrier generation, injection, transport and potentially dynamics in organic semiconductors.